2013
DOI: 10.1016/j.biopsych.2012.09.033
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Association Study of Depressive Symptoms

Abstract: Background Depression is a heritable trait that exists on a continuum of varying severity and duration. Yet, the search for genetic variants associated with depression has had few successes. We exploit the entire continuum of depression to find common variants for depressive symptoms. Methods In this genome-wide association study, we combined the results of 17 population-based studies assessing depressive symptoms with the Center for Epidemiological Studies Depression Scale. Replication of the independent to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
156
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 156 publications
(167 citation statements)
references
References 75 publications
(79 reference statements)
5
156
1
4
Order By: Relevance
“…There have been numerous reports of genetic associations between polymorphisms in clock genes and psychiatric disorders (including major depressive disorder and seasonal affective disorder) (6)(7)(8)(9)(10)(11)(12)(13)(14), but neither direct causal mutations nor molecular pathways have been identified. We previously reported that in a FASP kindred with a mutation in casein kinase 1δ, four of the five affected individuals exhibited higher depression scores (17) however, the mutant mice carrying the casein kinase 1δ mutation were not phenotyped for depression-like behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been numerous reports of genetic associations between polymorphisms in clock genes and psychiatric disorders (including major depressive disorder and seasonal affective disorder) (6)(7)(8)(9)(10)(11)(12)(13)(14), but neither direct causal mutations nor molecular pathways have been identified. We previously reported that in a FASP kindred with a mutation in casein kinase 1δ, four of the five affected individuals exhibited higher depression scores (17) however, the mutant mice carrying the casein kinase 1δ mutation were not phenotyped for depression-like behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, shift work has been suggested as a risk factor for major depressive disorder (3), and depression severity correlates with the degree of circadian misalignment (4,5). A number of genetic variants in core clock genes have been reported as statistically associated with mood disorders, including seasonal affective disorder and major depressive disorder (6)(7)(8)(9)(10)(11)(12)(13)(14), but to date none has been causally related with an understanding of specific molecular links.…”
mentioning
confidence: 99%
“…Considering the persistent lack of progress in core research areas such as antidepressant efficacy (Khan and Brown, 2015) and biomarkers robustly associated with depression diagnosis (Hek et al, 2013;Kapur et al, 2012), this topic deserves more attention in contemporary research.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…53 This is in addition to the finding that apparently healthy first-degree relatives of probands with major depressive episodes exhibit HPA dysregulation similar to that seen in affected relatives and different to the response seen in healthy controls. 54 The failure of genome wide association studies to identify relevant genetic polymorphisms (or for that matter any polymorphisms) associated with the HPA axis 55 is likely attributable to the complex relationship between the environmental and genetic factors that predispose to depression.…”
Section: Pierscionek Et Almentioning
confidence: 99%
“…AVP1b receptor, 62 11β-HSD1 receptor, 63 amino peptidase N (which controls AVP release), 55 and P-glycoprotein genes 64 also show an association with depression and response to antidepressant treatment. 65 Epigenetic changes that include DNA methylation are responsible for a reversible functional impact 66 causing changes in the expression of genes coding for AVP, 67 and FKBP5, 22 and can arise following trauma or adversity during critical developmental periods.…”
mentioning
confidence: 99%